Family presence during resuscitation: adaptation and validation into Spanish of the Family Presence Risk-Benefit scale and the Self-Confidence scale instrument - Eva de Mingo-Fernández; Ángel Belzunegui-Eraso; María Jiménez-Herrera (BMC, 2021)
Abstract Background Family Presence during Cardiopulmonary Resuscitation has been studied both to identify the opinions of health professionals, patients, and family members, and to identify benefits and barriers, as well as to design protocols for its implementation. R. Twibell and her team designed an instrument that measured nurses' perceptions of Risks-Benefits and Self-Confidence regarding Family Presence during Resuscitation. There are few studies in Spain on this practice. Methods The aim is to adapt and validate into Spanish the Family Presence Risk-Benefit scale and Family Presence Self-Confidence scale instrument. For this purpose, this instrument was translated cross-culturally, and administered in paper and online version. Statistical tests were carried out for the validity of the questionnaire. Five hundred forty-one healthcare professionals were invited to respond. The results were analyzed by the same statistical procedures as in the original scale. Ethical approvals and research permissions were obtained according to national standards. Results Two hundred thirty-seven healthcare professionals (43.8%) answered the survey (69% women), of whom 167 were nurses. Validation of instruments: Cronbach's α in Family Presence Risk-Benefit scale was 0.94. Cronbach's α in Family Presence Self-Confidence scale was 0.96. Factor Analysis Kaiser, Meyer and Olkin (KMO) was greater than 0.9. The correlation between the two measured scales, is significant and has a moderate intensity of the relationship (r = 0.65 and α < 0.001). A lower predisposition to Family Presence during Cardiopulmonary Resuscitation is observed, but the pure detractors are only 12%. Doctors are more reluctant than nurses. Conclusions The psychometric properties of the questionnaire in Spanish indicate high validity and reliability. Risk-Benefit perception and Self-Confidence are related to the healthcare professionals who consider the Family Presence to be beneficial. More studies in different contexts are necessary to confirm the psychometric results and validity of this instrument in Spanish.